Challenges in implementing School Based Assessment in the English language subject : an exploratory study of selected primary schools in Cheras - Fatimah binti Mohd Zain (Kulliyyah of Education, International Islamic University Malaysia, 2017)
The Malaysian education system has experienced tremendous transformation with the aim to produce knowledgeable students who are critical and creative in thinking and are capable to compete at national level. One of the major changes in the nation's education system is the implementation of the School Based Assessment through the Primary School Standard Curriculum as the new assessment practice besides the national examination. There have been numerous issues throughout the implementation of School Based Assessment since it was first introduced in 2011. The Ministry of Education placed great effort to cater the challenges faced by the teachers in implementing the School Based Assessment from time to time. This study aims at identifying the teachers' perception upon the implementation of School Based Assessment in the Primary School for English Language subject in Cheras, Kuala Lumpur. In this quantitative method research, a total of 62 participants; 60 females and 2 males from 50 schools in Cheras are selected to complete the survey in the form of questionnaire. The implications of this study will shed some light on how the teachers perceived the School Based Assessment is being implemented at primary school level by the teachers particularly in English Language subject after its fifth year. The teachers' clarity regarding the School Based Assessment is recognized. What the teachers knew about the amendments made by the Ministry of Education is also discussed in the findings. The challenges that the teachers still faced after its fifth year of implementation are identified. Suggestions from the respondents to improve the SBA are included in the discussion.